Prediction of tannin profile in grape (Vitis vinifera L.) skins during berry maturation using a rapid mechanical puncture approach. (15th August 2022) - Duan, Bingbing; Chen, Guoqiao; Jin, Xiaoduo; Chang, Wei; Lan, Tian; Zhao, Yimei; Sun, Xiangyu; Liu, Xu
Graphical abstract: Highlights: Dynamic variations of condensed tannin were investigated as maturation progressed. Mechanical properties showed a good correlation with the specific condensed tannin characteristics. Random forest served as an excellent model for evaluating skin condensed tannin profile. PCA and OPLS-DA obtained excellent classification results for the ripe and unripe samples. Abstract: Tannin structure and composition are variable during grape maturation, and crucially determine perceived astringency, body structure and aging capacity of red wines. This study investigated the evolution of condensed tannins (CTs) in grape skins as maturation progressed and the feasibility of using a rapid mechanical puncture approach for assessing the CTs profile. The results showed that the mean degree of polymerization (mDP), molecular mass (MM), and proportions of (–)-epigallocatechin in extension subunits (EGC_ext) and (–)-epicatechin-3- O -gallate in terminal subunits (ECG_term) of skins increased during grape maturation, while CTs content and the proportion of (–)-epicatechin-3- O -gallate in extension subunits decreased. The predictive models built by random forest for CTs content based on skin weight, mDP, MM_subunit, EGC_ext, and ECG_term obtained good results with high squared correlation coefficients of prediction and calibration (R 2 _P > 0.85 and R 2 _C ≈ 0.95). In addition, the classifications of CTs characteristics obtained from ripe and unripe samples were observed in different principal component spaces. This study indicated that the mechanical properties were useful for predicting skin CTs profile, estimating tannin maturity stages, and providing information for optimal harvesting and winemaking protocols.